Submarine groundwater discharge drives coastal water quality and nutrient budgets at small and large scales - Zhang, Yan; Santos, Isaac R.; Li, Hailong; Wang, Qianqian; Xiao, Kai; Guo, Huaming; Wang, Xuejing (Geochimica et cosmochimica acta, 2020)
•Location of polluted nearshore waters coincided with SGD hotspots on a local scale.•SGD-driven nutrients were one order of magnitude higher than riverine inputs in China.•Nutrients via SGD contributed >50% of the total sources to Chinese coastal waters.•SGD influences coastal water quality and nutrient budgets at small and large scales. Submarine groundwater discharge (SGD) can be a significant source of chemical pollutants from land to ocean. Here, we first estimated SGD using radium isotopes and related nutrient fluxes at the local scale in Jiaozhou Bay (JZB), a typical Chinese system that is experiencing rapid urban and industrial development. We then summarized SGD studies off China to assess the large-scale implications of SGD to nutrient budgets. In JZB, the location of contaminated nearshore waters revealed by an integrative water quality index (WQI) coincided with the SGD hotspots. The total (fresh and saline) SGD flux in JZB was estimated to be (0.64–1.67) × 107 m3/d or (2.12–5.59) cm/d based on 224Ra and 228Ra mass balance models. This was approximately 8 times the discharge rate of local rivers. By combining these JZB results with the literature data, we provide the first estimate of SGD and associated nutrient fluxes off China. The magnitude of SGD at the China-scale was (5.40–10.2) × 1012 m3/yr, accounting for 5–9% of the global SGD flux. SGD-derived nutrient fluxes summarized from ∼40 previous studies were one order of magnitude higher than riverine inputs. These nutrients fluxes from SGD contributed >50% of the total dissolved inorganic nitrogen (DIN), phosphorous (DIP) and silicate (DSi) inputs into Chinese coastal waters, which can explain about 60% of the phosphorus required by primary production. The mean DIN/DIP ratio (121) in SGD was significantly higher than the Redfield ratio, with important implications for phytoplankton growth and structure. SGD can influence water quality, dominate nutrient budgets, and drive primary production not only at the local scale, but also at the regional and global scales.